Public Transportation Strategy in Response to Covid-19 - Farizd, Miftah; Wahyuni, Chatarina Umbul; Yamani, Laura Navika (Journal of Social Research, 2023)
The COVID-19 pandemic has had a significant impact on public transportation worldwide. At the beginning of the pandemic, public transportation systems reduced their performance by 80-90% in major cities in China, Iran, and the United States, and by 70% in the UK, including a significant decline in Indonesia. Several studies have shown that public transportation contributes significantly to the spread of the COVID-19 virus. This study aims to review the use of public transportation during the COVID-19 pandemic. Method: A systematic review using the PRISMA guidelines was conducted on literature published between 2020-2023 with inclusion criteria of national and international research articles in English related to the title "Public Transportation Strategy in Response to COVID-19". The database sources used were Scopus, Google Scholar, and PubMed. Results: Based on the literature review, it is concluded that efforts to reduce the risk of COVID-19 transmission in public transportation include providing personal protective equipment (PPE) for all public transportation crew, implementing strict physical distancing policies among passengers inside the vehicle, ensuring good ventilation, and enforcing the use of masks and hand hygiene. Another solution is to provide non-cash payment options to reduce physical contact between passengers and transportation personnel. The government and public transportation operators should consistently prepare supporting facilities and educate users about physical distancing, using masks, and hand hygiene through posters, social media, and regular announcements in public transportation areas. Implementing strategies in public transportation in response to COVID-19 requires collaboration between the government, transportation operators, and the public.